IMPLEMENTASI MODEL PEMBELAJARAN BERBASIS PENGALAMAN PADA MATA KULIAH KONSEP DASAR IPS JURUSAN PGSD UNIVERSITAS MUSAMUS - Rival Hanip; Eva Nirtha; Andika Wahyudiono (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
Experiential learning model or known as "Experiential Learning" is a learning process that bases knowledge acquisition based on experience. The purpose of this study is to determine the implementation of an experience-based learning model in the basic concepts of social studies at Musamus University. The data collection techniques used were interviews and documentation. The experience-based learning model in the basic concepts of social studies courses can be carried out well and get positive enthusiasm from students.